2006
DOI: 10.28945/479
|View full text |Cite
|
Sign up to set email alerts
|

A Systems Approach to Conduct an Effective Literature Review in Support of Information Systems Research

Abstract: This paper introduces a framework for conducting and writing an effective literature review. The target audience for the framework includes information systems (IS) doctoral students, novice IS researchers, and other IS researchers who are constantly struggling with the development of an effective literature-based foundation for a proposed research. The proposed framework follows the systematic data processing approach comprised of three major stages: 1) inputs (literature gathering and screening), 2) processi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
737
0
48

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 942 publications
(880 citation statements)
references
References 48 publications
1
737
0
48
Order By: Relevance
“…A methodological review of past literature is a "crucial endeavour" (Webster and Watson 2002) for any academic research, and it is vital that this is done in a rigorous and comprehensive manner (Webster and Watson 2002, Walsham 2006, Levy 2006. The literature analysis strategy and approach is rarely given much attention, with most papers elaborating more on the empirical data collection and analysis phases of the research.…”
Section: Research Approachmentioning
confidence: 99%
“…A methodological review of past literature is a "crucial endeavour" (Webster and Watson 2002) for any academic research, and it is vital that this is done in a rigorous and comprehensive manner (Webster and Watson 2002, Walsham 2006, Levy 2006. The literature analysis strategy and approach is rarely given much attention, with most papers elaborating more on the empirical data collection and analysis phases of the research.…”
Section: Research Approachmentioning
confidence: 99%
“…In order to answer the research question, a literature review was carried out according to Levy and Ellis (2006). The following databases were researched for scientific literature from the areas business informatics, forestry, timber as well as pulp and paper industry: HoWiLit, ACM Portal, CiteSeer, EbscoHost, Elsevier, IEEE Xplore, InderScience, JSTOR, ProQuest, ScienceDirect, SpringerLink, and Wiley Online Library.…”
Section: Related Methodsologymentioning
confidence: 99%
“…Those lacking empirical tests were excluded. Backward references [36] provided further publications. One of the authors of a recent literature review [34] provided an appendix of literature focused on motivating information security policy compliance in organizations.…”
Section: A Behaviour-change In Information Securitymentioning
confidence: 99%
“…1) Literature Review: Using the methodology in [31], we searched for literature using the terms 'behaviour change' and 'information security'. From notable research repositories providing access to peer-reviewed literature [36], we identified papers published from the year 2000 to date. Those lacking empirical tests were excluded.…”
Section: A Behaviour-change In Information Securitymentioning
confidence: 99%